Pengaruh Model Pembelajaran IOC (Inside Outside Circle) Terhadap Hasil Belajar Siswa Kelas V Gugus 04 Kecamatan Pujut pada Pembelajaran IPS Tahun Pelajaran 2020/2021 - Anti, Rahmawanti; Nasarudin, Nasarudin; Oktaviyanti, Itsna (Jurnal Ilmiah Pendidikan Indonesia, 2020)
This research is an experimental research (Quasi Experiment) which aims to determine the effect of the Inside Outside Circle model on the learning outcomes of class V students at SDN Gugus 04, Pujut District in the Social Studies Learning 2020/2021 academic year. This research design using Nonequivalent control group design. The population in this study were all fifth grade students of SDN Gugus 04 Pujut District. The sampling technique used was purposive sampling, the sample was class V SDN 2 Truwai as the experimental class and class V SDN Bedus as the control class. Data collection methods used were observation and learning outcome tests. Student learning outcomes data in the form of pretest and posstest. The normality test is carried out by calculating the data in the form of the pretest and posttest results, then after the data is normally distributed, the homogeneity test is carried out which is obtained from the results of the posttest data calculation, then the hypothesis test is carried out using the t test using the calculation of the student's posttest data. Based on the data on learning outcomes analyzed using the t-test (t-test), the t-test was 2.547 while the t-table was 2015 at the 5% confidence level. This explanation shows that t count is greater than t table so it can be concluded that Ha is accepted and H0 is rejected. This shows that there is an influence of the Inside Outside Circle model on student learning outcomes. Furthermore, in the effect size test with a value of 2.57 with high criteria because> 1.00 based on the calculation of Cohen's effect size value.